Organizational Readiness for the Implementation of Multilevel School Mental Health Support Systems; [Preparación Organizacional Para Implementar Sistemas de Apoyo en Múltiples Niveles en Salud Mental Escolar] - Rojas-Andrade, R (Pontificia Universidad Catolica de Valparaiso, 2023)
School mental health relies on Multi-Level Systems of Support. To implement them successfully, schools must be prepared. However, research has paid little attention to this process. The purpose of this study was to analyze the organizational readiness to implement these systems in public schools by school administrators and psychosocial intervention professionals (e.g., psychologists and social workers) in a school district in Chile. A total of 178 participants from 54 public schools participated. The Organizational Readiness for Change Implementation Scale and the Implementation Determinants Survey were applied online. A high level of commitment to implementation was found, but a low level of capacity to carry out the changes. Regarding implementation, it was found that psychosocial professionals perceive a low level of technical empowerment compared to coordination, as well as low perceived support from the educational community. In all dimensions, the managers scores were higher. It is argued that schools are not yet ready to implement multilevel support systems, and that it is necessary to invest in greater implementation supports and in instances that allow closing the gap in the perception of principals and staff. © 2023 Pontificia Universidad Catolica de Valparaiso. All rights reserved.